2016
DOI: 10.3892/ijo.2016.3469
|View full text |Cite
|
Sign up to set email alerts
|

CLDN6-induced apoptosis via regulating ASK1-p38/JNK signaling in breast cancer MCF-7 cells

Abstract: Claudin 6 (CLDN6), a member of tight junction protein claudin (CLDN) family, inhibits proliferation and induces apoptosis of MCF-7 breast cancer cells. However, these molecular mechanisms of CLDN6-induced apoptosis remain largely elusive. We previously found that restoration of human CLDN6 gene expression was correlated with the expression level of apoptosis signal-regulating kinase 1 (ASK1) using cDNA array and bioinformatics analysis. ASK1, a mitogen-activated protein kinase kinase kinase, is involved in env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 46 publications
2
25
0
Order By: Relevance
“…Phosphorylation of p38 during cell death has been reported on a number of occasions [56][57][58][59][60]. Furthermore, several research teams have shown p38 activation is linked with caspase-independent cell death mediated by the nuclear translocation of AIF [56,59,61,62].…”
Section: Discussionmentioning
confidence: 97%
“…Phosphorylation of p38 during cell death has been reported on a number of occasions [56][57][58][59][60]. Furthermore, several research teams have shown p38 activation is linked with caspase-independent cell death mediated by the nuclear translocation of AIF [56,59,61,62].…”
Section: Discussionmentioning
confidence: 97%
“…Tight junctions could be disrupted or 'loosened' in cancer cells in order to induce dissemination and migration during the cancer metastatic process. Therefore, claudins, including CLDN1, CLDN3, CLDN4, CLDN6, CLDN7, CLDN10, CLDN14 and CLDN17, serve a critical role in modulating carcinogenesis and metastasis (28)(29)(30)(31)(32)(33)(34)(35)(36)(37). In a previous study, CLDN10 was reported to suppress cell metastasis by phosphorylating the Janus kinase 1/signaling transducer and activator of transcription 1 signaling pathway in osteosarcoma cells (38).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it was observed that miR‐655 suppresses EMT via targeting Prrx1 in triple‐negative BC (Lv et al, ). Also, very recently it was identified that claudins (CLDN6) inhibits the malignant progression and induces apoptosis in mammary tumor cells via the p38/MAPK pathway and ASK1 signaling, respectively (Guo et al, ; Q. Wu et al, ).…”
Section: Antimetastatic Mirnas In Breast Cancermentioning
confidence: 99%